Clinical characteristics and quality of life, depression, and anxiety in adults with neurofibromatosis type 1: A nationwide study. Issue 7 (2nd June 2020) - Doser, Karoline; Andersen, Elisabeth Wreford; Kenborg, Line; Dalton, Susanne Oksbjerg; Jepsen, Jens Richardt Møllegaard; Krøyer, Anja; Østergaard, John; Hove, Hanne; Sørensen, Sven Asger; Johansen, Christoffer; Mulvihill, John; Winther, Jeanette Falck; et al.
Abstract: Neurofibromatosis type 1 (NF1) is a genetic condition characterized by numerous somatic manifestations. The psychosocial burden in adults has rarely been studied. We examined the prevalence of self‐reported impairment of quality of life (QoL), symptoms of anxiety and depression and need for support, associated with disease severity and visibility. We conducted a nationwide cross‐sectional study of all 467 adults with NF1 diagnosed between 1977 and 2016 at one of the two national centers for rare diseases in Denmark. A total of 244 (56% response rate) completed a questionnaire that included standard measures of QoL, symptoms of depression and anxiety, indicators of disease‐related severity, visibility, and need for professional support. Associations between disease severity and visibility and psychosocial burden were analyzed in descriptive and multivariate models. We observed impaired QoL (mean = 81.3; 95% CI, 76.2; 86.4); 19% reported symptoms of depression (mean = 5.7; SD = 5.4), and 15% reported anxiety (mean = 5.1; SD = 5.2) at a clinical level. Adults with NF1 also reported requiring professional support for physical, psychological, and work‐related problems. Disease severity and (partly) visibility were significantly ( p < .0001) associated with psychosocial well‐being and a requirement for support. This study provides new understanding of the factors associated with impaired QoL, indicating that follow‐up care should be optimized into adult life.